Analysis of Student Loss Character After Online Learning Class III and VI Elementary School (Phenomenological Study at SD Negeri Tritih Wetan 05 Jeruklegi Cilacap District) - Vitasari, Rizka; Andriani, Ana (Proceedings Series on Social Sciences & Humanities, 2023)
At the end of 2019, it was the hardest year for countries around the world, including Indonesia. The Corona virus outbreak or Covid-19 hit and has an impact on all aspects of life, one of which is the aspect of education. The government through the Ministry of Education immediately took steps to stop conventional learning in an effort to stop the rate of mutation of the virus. The government opened limited access to Post-Online or Face-to-Face Learning (PTM) gradually by encouraging Yellow Zone and Green Zone schools to implement limited Face-to-Face Learning. Distance learning also results in setbacks, namely in the character of students. Subject of this research were third and sixth grade elementary school students in Jeruklegi Subdistrict, Cilacap Regency, Indonesia. This research used qualitative method. Techniques of collecting data of this research were observation, interview, and documentation studies.The analysis data tecniques used in the study is the Miles and Huberman interactive analysis model. From this research, it can be concluded that the online learning can cause the loss character of students.